Research Progress on the Mechanism of Natural Product Ingredients in the Treatment of Uveitis - Sicong Li (Hindawi Limited, 2021)
Background. As the spectrum of ophthalmic diseases keeps changing, uveitis has gradually become one of the major blinding eye diseases in the world. In recent years, it has become a research hotspot to select effective components for uveitis treatment from natural drugs. Methods. We searched PubMed and EMBASE databases for studies written in English as well as Chinese National Knowledge Infrastructure (CNKI), CQVIP, and Wan Fang database for studies written in Chinese (inception through 30 December 2020). Results. Eight kinds of natural product ingredients were included in this article. They were found to not only regulate the expression of cytokines, proliferation, and differentiation of T help cells but also inhibit the damage of cytokines and inflammatory cells to uvea, blood aqueous barrier, and blood retinal barrier. Conclusion. Natural product ingredients have their unique advantages in the treatment of uveitis. They have good anti-inflammatory effects without causing serious adverse reactions, which enables them to be promising choices for preventive and therapeutic strategy of uveitis.